Francisella DnaK Inhibits Tissue-nonspecific Alkaline Phosphatase - Arulanandam, Bernard P. (American Society for Biochemistry and Molecular Biology, 2012)
Following pulmonary infection with Francisella tularensis, we observed an unexpected but significant reduction of alkaline phosphatase, an enzyme normally up-regulated following inflammation. However, no reduction was observed in mice infected with a closely related Gram-negative pneumonic organism (Klebsiella pneumoniae) suggesting the inhibition may be Francisella-specific. In similar fashion to in vivo observations, addition of Francisella lysate to exogenous alkaline phosphatase (tissue-nonspecific isozyme) was inhibitory. Partial purification and subsequent proteomic analysis indicated the inhibitory factor to be the heat shock protein DnaK. Incubation with increasing amounts of anti-DnaK antibody reduced the inhibitory effect in a dose-dependent manner. Furthermore, DnaK contains an adenosine triphosphate binding domain at its N terminus, and addition of adenosine triphosphate enhances dissociation of DnaK with its target protein, e.g. alkaline phosphatase. Addition of adenosine triphosphate resulted in decreased DnaK co-immunoprecipitated with alkaline phosphatase as well as reduction of Francisella-mediated alkaline phosphatase inhibition further supporting the binding of Francisella DnaK to alkaline phosphatase. Release of DnaK via secretion and/or bacterial cell lysis into the extracellular milieu and inhibition of plasma alkaline phosphatase could promote an orchestrated, inflammatory response advantageous to Francisella.